2018
DOI: 10.1002/app.46188
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Syzygium cumini leaves extract on morphological, thermal, mechanical, and antimicrobial properties of PVA and PVA/chitosan blend films

Abstract: In the present work, poly(vinyl alcohol)/Syzygium cumini leaves extract (PSN) and poly(vinyl alcohol)/chitosan/S. cumini leaves extract blend films were prepared by solution casting technique. The films were characterized by using scanning electron microscopy, atomic force microscopy, X-ray diffraction study, Fourier transform infrared spectroscopy, thermogravimetric analysis, and universal testing machine. The results indicated that the appreciable physical interaction at lower concentrations of S. cumini lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 62 publications
4
35
0
Order By: Relevance
“…A negative correlation existed between properties T s , Y m, E b and content of SC bud fluid, that is an increase in the volume of SC bud fluid in the PVA matrix led to decreased T s , Y m , and E b . The present findings of this study are in good agreement with the literature reported by other researchers [36,38]. The results are relatable with the FTIR study.…”
Section: Tensile Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…A negative correlation existed between properties T s , Y m, E b and content of SC bud fluid, that is an increase in the volume of SC bud fluid in the PVA matrix led to decreased T s , Y m , and E b . The present findings of this study are in good agreement with the literature reported by other researchers [36,38]. The results are relatable with the FTIR study.…”
Section: Tensile Propertiessupporting
confidence: 93%
“…Which may be due to the weak molecular interaction between the polar groups of SC bud fluid and -OH group of PVA. The decrease in T s , Y m , and E b at higher loading of SC bud fluid attributed to the insufficient interaction and bad compatibility or non-homogeneous dispersion induced by the SC bud fluid [17,36,37]. A negative correlation existed between properties T s , Y m, E b and content of SC bud fluid, that is an increase in the volume of SC bud fluid in the PVA matrix led to decreased T s , Y m , and E b .…”
Section: Tensile Propertiesmentioning
confidence: 97%
“…Since acetate groups are larger than -OH groups, PVA with a low degree of hydrolysis exhibits lower crystallinity. As such, a highly hydrolyzed PVA is more crystalline than partially hydrolyzed PVA and presents higher glass transition and melting temperatures [81][82][83][84][85][86]. The effect of the molecular weight and the degree of hydrolysis on the properties of PVA is highlighted in Table 2.…”
Section: Poly(vinyl Alcohol)mentioning
confidence: 99%
“…The effect of the molecular weight and the degree of hydrolysis on the properties of PVA is highlighted in Table 2. Even though PVA is one of the oldest synthetic polymers, it continues to be frequently used in advanced biomedical applications because of its excellent biocompatibility, biodegradability, excellent transparency, film forming abilities, thermo-stability and chemical resistance [81][82][83][84][85][86]. Nevertheless, its restricted strength, low thermal stability and instant dissolution or excessive swelling in aqueous environments has limited its application and made the crosslinking process indispensable [88][89][90].…”
Section: Poly(vinyl Alcohol)mentioning
confidence: 99%
“…In the FTIR spectrum of native PVA, bands seen at 2947 and 2907 cm −1 are assigned to C─H and CH 2 asymmetric stretching vibrations of PVA. The shifting in aliphatic C─H stretching vibration in the FTIR spectra of the nanocomposite films compared to the FTIR spectra of the native polymers proves that a strong interaction exists among the native polymers and ZnO microparticles …”
Section: Resultsmentioning
confidence: 97%